Computer Hardware and Software Education for Teacher's Office of Insan Mulia Early Childhood Education School Tangerang - Lukman Medriavin Silalahi; Imelda Uli Vistalina Simanjuntak; Setiyo Budiyanto; Agus Dendi Rochendi (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2023)
This community service proposed assistance from competent instructors to educate participants to get to know computer hardware and software, ranging from variations, and models, to supporting components based on the research approach method in the electrical engineering field. The training participants were ECE (Early Childhood Education) teachers of Insan Mulia PAUD School. This CS (Community Service) program aimed to educate the ECE teachers of the school to keep up with the advancement of computer technology. Thus, the contribution of this activity was to improve the quality of skilled labor and align with industry needs. Therefore, a Computer Hardware and Software Education activity was held at the Teacher's Office of Insan Mulia Early Childhood Education School in Tangerang. The Research and Community Service of Universitas Mercu Buana participated in this activity by carrying out the ICT (Information and Communication Technology) theme in the RMP (Research Master Plan), the long-term target is the development of wireless sensors and actuators, to the integration of system implementation. In conclusion, this activity produced new skills for Insan Mulia ECE School teachers in the knowledge of computer hardware and software as well as the installation of required computer devices that have operated very well.